Personality traits and public support of minority rights. Issue 3 (17th February 2021) - Ziller, Conrad; Berning, Carl C.
ABSTRACT: This study investigates how personality relates to citizens' willingness to extend political, social, and cultural rights for minorities, including voting rights for immigrants, religious rights for Muslims, and affirmative action measures. Moving beyond explanations centred on intergroup relations, we argue that political efficacy (i.e. beliefs about personal political competences and the responsiveness of political elites) operates as a mechanism linking personality and policy preferences on minority rights. We test these arguments using mediation models on data from a large-N survey conducted in Germany in 2016. Results show that high openness, high agreeableness, and low conscientiousness predict permissive views on minority rights. In addition to indirect effects via group-specific attitudes, we find empirical support for substantial links via political efficacy. In particular, people high in conscientiousness or high in neuroticism have lower faith in government responsiveness, which in turn is related to less willingness to approve minority rights.